Atypical presentation of cryptococcal meningitis in oncology patients: Case Report - Wei, Jing; Huang, Haiyan; Zhang, Yingyu; Huang, Yanlan; Liang, Yingfang; Jiang, Shan (Frontiers in Medicine, 2025)
Cryptococcal meningitis (CM) is a serious central nervous system (CNS) infection primarily affecting immuno-compromised individuals, including cancer patients. Although rare in oncology populations, it may present atypically and pose diagnostic challenges. We report two cases of malignancy-associated CM with non-classical features. The first involved a male with lung squamous cell carcinoma and multiple comorbidities, presenting with mild cerebrospinal fluid (CSF) pleocytosis and normal opening pressure. The second case involved a female with chronic lymphocytic leukemia and concurrent cryptococcal and purulent meningitis, showing marked leukocytosis and elevated CSF pressure. Neither had recent antitumor therapy. Despite similar initial symptoms of fever and headache, their clinical courses diverged: the male recovered with antifungal treatment, while the female had a poor response and discontinued therapy. These cases highlight the variable and atypical nature of CM in cancer patients and underscore the importance of early recognition and inclusion of fungal infections in the differential diagnosis for CNS complications, even in the absence of classical features.